Lithium battery positive electrode, preparation method thereof and solid-state battery

By designing a current collector with a three-dimensional porous structure in the positive electrode of the lithium battery and filling the positive electrode composite material, the problem of insufficient ionic conductivity and mechanical properties of the solid polymer electrolyte is solved, efficient electron transport and good dispersion of active substances are achieved, and the overall performance of the battery is improved.

CN119920824APending Publication Date: 2025-05-02CHONGQING TALENT NEW ENERGY CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411736322.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

The low ionic conductivity and poor mechanical properties of solid polymer electrolytes in existing lithium-ion batteries lead to poor electrochemical performance of the battery and are easily penetrated by dendrites, which reduces the overall performance of the battery.

Method used

A lithium battery positive electrode with a three-dimensional porous structure is designed. By filling the positive electrode composite material in the three-dimensional framework, a continuous conductive network is formed to achieve the effect of conducting both electrons and ions, while limiting the agglomeration of active substances and maintaining a good dispersion state.

Benefits of technology

It improves the rapid transmission of electrons inside the electrode, enhances the storage space of lithium ions, maintains the reactive activity of active substances, and improves the performance stability and electrochemical performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_2
    Figure SMS_2
  • Figure QLYQS_1
    Figure QLYQS_1
Patent Text Reader

Abstract

The invention relates to the technical field of solid-state batteries, in particular to a lithium battery positive electrode, a preparation method thereof and a solid-state battery. The lithium battery positive electrode comprises a positive electrode composite material and a current collector with a three-dimensional porous structure, wherein pores of a three-dimensional skeleton of the current collector are filled with the positive electrode composite material, and the three-dimensional skeleton is generated by a polymer solid electrolyte. According to the invention, the current collector with a three-dimensional structure is designed, so that the positive electrode composite material permeates into a three-dimensional skeleton, and the effects of conducting electrons and ions can be realized through mutual permeation. Meanwhile, the three-dimensional structure can limit agglomeration of active substances, so that the active substances are kept in a good dispersion state in the charging and discharging process. The reaction activity of the active substance can be maintained, and the performance stability of the battery can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of solid-state batteries, and in particular to a lithium battery positive electrode and a preparation method thereof, and a solid-state battery. Background Art

[0002] With the widespread use of portable electronic devices such as mobile phones, laptops, and tablets, higher requirements are placed on the energy density, endurance, and safety of batteries. Lithium metal batteries have become a potential choice to meet these requirements due to their high theoretical specific energy, which has promoted the research and development of lithium metal battery cathode materials to improve the overall performance of batteries and meet the growing energy needs of portable electronic devices.

[0003] In recent years, the electric vehicle market has shown a rapid growth trend. Electric vehicles require high-performance batteries to provide sufficient mileage and power. The high energy density characteristics of lithium metal batteries make them have great application potential in the field of electric vehicles. Therefore, in order to meet the requirements of electric vehicles for battery performance, the research and development of lithium metal battery positive electrodes has become particularly important.

[0004] In terms of battery manufacturing processes and technologies, continuous improvements and innovations have also provided support for the development of lithium metal battery cathodes. For example, improving electrode preparation methods can increase the loading capacity and utilization rate of cathode materials, and optimizing battery structural design can improve battery safety and stability.

[0005] Solid electrolytes in lithium-ion batteries can better solve the safety issues of the above-mentioned liquid electrolytes. Solid electrolytes have flame retardant properties and can greatly improve battery safety. Among them, solid polymer electrolytes are a type of solid electrolytes, which are widely used in solid-state batteries due to their good flexibility and good contact with electrodes. However, the low ionic conductivity and poor mechanical properties of solid polymer electrolytes make them easily penetrated by dendrites, thereby greatly reducing the electrochemical performance of the battery. Summary of the invention

[0006] The present invention aims to solve one of the technical problems in the prior art at least to a certain extent. To this end, the object of the present invention is to provide a lithium battery positive electrode and a preparation method thereof and a solid-state battery.

[0007] Based on this, the present invention has the following technical solutions: In a first aspect, the present invention provides a lithium battery positive electrode, comprising: a positive electrode composite material and a current collector having a three-dimensional porous structure; wherein the positive electrode composite material is partially filled in the pores of the three-dimensional skeleton of the current collector, and the three-dimensional skeleton comprises a polymer solid electrolyte.

[0008] The present invention designs a current collector with a three-dimensional structure so that the positive electrode composite material can penetrate into the three-dimensional skeleton, and can penetrate each other to achieve the effect of conducting both electrons and ions. Specifically, the positive electrode material with the three-dimensional structure can form a continuous conductive network, so that electrons can be efficiently transmitted from the current collector to various parts of the active material, reducing the resistance and energy loss during the electron transmission process, which helps the rapid transmission of electrons inside the electrode. And the rich pores and surface structures inside the positive electrode material with a three-dimensional porous structure provide a large amount of space for the storage of lithium ions, so that the battery can store more electrical energy. At the same time, the three-dimensional structure can limit the agglomeration of active materials, so that the active materials can maintain a good dispersion state during the charge and discharge process, which helps to maintain the reactivity of the active materials and improve the performance stability of the battery.

[0009] Preferably, the amount of the polymer solid electrolyte used is less than the amount of the positive electrode composite material used.

[0010] More preferably, the mass ratio of the polymer solid electrolyte to the positive electrode composite material is (3-4): (6-7).

[0011] The present invention finds that the amount of the polymer solid electrolyte is less than the amount of the positive electrode composite material to ensure that the active material layer can penetrate into the three-dimensional layer of the solid electrolyte as much as possible, and the amount of the solid electrolyte layer is not too small, otherwise the three-dimensional structure layer provided is small and the effect is not obvious; the polymer solid electrolyte and the positive electrode composite material are controlled under the above-mentioned dosage relationship to form a uniform three-dimensional positive electrode layer, thereby achieving the effect of both conducting electrons and ions.

[0012] In the present invention, the three-dimensional skeleton of the current collector is generated by a polymer solid electrolyte. Specifically, those skilled in the art can use methods such as electrospinning and melt-blowing to introduce the polymer solid electrolyte into the current collector layer to form a three-dimensional skeleton.

[0013] Preferably, a material containing a polymer solid electrolyte is sprayed onto a current collector by a melt-blowing method to form the current collector having a three-dimensional porous structure.

[0014] As a preferred embodiment of the present invention, when the polymer solid electrolyte is sprayed onto the current collector by melt-blowing, the specific parameters include: the receiving angle of the transmission receiver to the melt-blown filament bundle is 0~90°, the receiving distance is 10~60cm, the spinneret aperture is 0.15~0.4mm, the compressed air temperature is 250~300℃, the melt-blowing temperature is 220℃~300℃, and the time is 2min~6min.

[0015] Preferably, the porosity of the three-dimensional skeleton is 40% to 80%, specifically 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, or a numerical range with any two of the above values ​​as endpoints.

[0016] The present invention finds that, compared with other methods, the use of the melt-blowing method can construct a three-dimensional skeleton, increase the specific surface area, shorten the process flow, form a uniform three-dimensional mesh, and is more conducive to controlling the above-mentioned porosity.

[0017] Preferably, the method for preparing the polymer solid electrolyte comprises: mixing an unsaturated sulfonic acid ester monomer, a catalyst, a lithium salt and a first organic solvent, and performing a polymerization reaction at 60-80°C.

[0018] In the present invention, the polymerization reaction temperature can be 60°C, 65°C, 70°C, 75°C, 80°C, etc., or a range between any two of the above values.

[0019] Preferably, the unsaturated sulfonate monomer has a structure shown in general formula (I): (I); wherein R and R' are each independently, the same or different, a fluorine atom, a hydroxyl group, a substituted or unsubstituted C1-C6 alkyl group, a substituted or unsubstituted C1-C6 alkoxy group, a substituted or unsubstituted C2-C6 alkenyl group, a substituted or unsubstituted C 6~ C 30 R and R' are bonded to form a ring, fused to form a ring or not formed into a ring.

[0020] Preferably, the unsaturated sulfonate monomer includes one or more of 2-phenylethylenesulfonyl fluoride, 1,3-propane sultone, vinylbenzenesulfonic acid, allyl allylsulfonate, 2,2-difluorovinyl-4-methylbenzenesulfonate and allyl p-toluenesulfonate.

[0021] The present invention finds that the use of the above-mentioned unsaturated sulfonate monomer in the system of the present invention can prevent the deposition and precipitation of metal ions by forming a complex with metal ions such as lithium ions, thereby inhibiting the dendrite growth of the battery and the instability of the solid electrolyte interface, thereby improving the safety and cycle life of the battery.

[0022] More preferably, based on the mass of the positive electrode composite material, the amount of the unsaturated sulfonate monomer is 30wt%~50wt%, specifically 30wt%, 35wt%, 40wt%, 45wt%, 50wt%, etc., or a numerical range with any two of the above values ​​as endpoints.

[0023] Preferably, the lithium salt includes at least one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(trifluoromethylsulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium bis(oxalatoborate), lithium difluorooxalatoborate and lithium trifluoromethanesulfonate.

[0024] More preferably, the lithium salt is lithium bis(trifluoromethanesulfonyl)imide and / or lithium bis(oxalatoborate).

[0025] More preferably, based on the mass of the unsaturated sulfonate monomer, the amount of the lithium salt is 30wt% to 60wt%, specifically 30wt%, 35wt%, 40wt%, 45wt%, 50wt%, 55wt%, 60wt%, etc., or a numerical range with any two of the above values ​​as endpoints.

[0026] The present invention finds that the above-mentioned lithium salt is more conducive to reducing the side reaction between the solid electrolyte membrane and the positive electrode, thereby reducing the capacity decay of the battery during the charge and discharge process, extending the service life of the battery, and further improving the overall performance of the battery.

[0027] Preferably, the catalyst includes one or more of aluminum trichloride, palladium chloride, palladium acetate, nickel dichloride, boron trifluoride, triethylamine, ferric bromide, ferric chloride, titanium tetrachloride and tin tetrachloride.

[0028] More preferably, based on the mass of the unsaturated sulfonate monomer, the amount of the catalyst is 0.1wt% to 5wt%, specifically 0.1wt%, 0.5wt%, 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, 4.5wt%, 5wt%, etc., or a numerical range with any two of the above values ​​as endpoints.

[0029] Preferably, the first organic solvent comprises one or more of diethyl ether, ethanol, acetonitrile, N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, tetrahydrofuran, malononitrile, succinonitrile, glutaronitrile, adiponitrile, pimelonitrile, suberonitrile, azelaic acid dinitrile and sebacononitrile.

[0030] Preferably, the polymerization time of the polymerization reaction is 3 to 6 hours.

[0031] In a second aspect, the present invention provides a method for preparing the positive electrode of a lithium battery, comprising: S1: mixing an unsaturated sulfonic acid ester monomer, a catalyst, a lithium salt and a first organic solvent, and performing a polymerization reaction at 60-80° C. to obtain a mixed solution; S2: The mixed solution is sprayed onto a current collector by a melt-blowing method, and after drying, a current collector having a three-dimensional porous structure is obtained.

[0032] S3: Mixing the positive electrode main material, the conductive agent, the binder and the second organic solvent, coating the obtained mixed slurry on the three-dimensional current collector obtained in S2, and obtaining the lithium battery positive electrode after drying.

[0033] Preferably, the first organic solvent comprises one or more of diethyl ether, ethanol, acetonitrile, N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, tetrahydrofuran, malononitrile, succinonitrile, glutaronitrile, adiponitrile, pimelonitrile, suberonitrile, azelaic acid dinitrile and sebacononitrile; and the second organic solvent comprises N-methylpyrrolidone.

[0034] Preferably, the lithium salt includes at least one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(trifluoromethylsulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium bis(oxalatoborate), lithium difluorooxalatoborate and lithium trifluoromethanesulfonate.

[0035] Preferably, the catalyst comprises one or more of aluminum trichloride, palladium chloride, palladium acetate, nickel dichloride, boron trifluoride, triethylamine, ferric bromide, ferric chloride, titanium tetrachloride and tin tetrachloride.

[0036] In the present invention, the positive electrode main material can be one or more of nickel-cobalt-manganese ternary material, nickel-cobalt-aluminum ternary material, lithium iron phosphate, lithium cobalt oxide, lithium manganate, and lithium vanadium phosphate; the conductive agent can be one or more of carbon black, single-walled carbon nanotubes, multi-walled carbon nanotubes, graphene, and carbon fiber; the binder can be one or more of polyvinylidene fluoride, polyamide resin, polyacrylonitrile, sodium carboxymethyl cellulose, and styrene-butadiene rubber. Those skilled in the art can make a selection according to actual conditions, and no specific limitation is made here.

[0037] As a preferred embodiment of the present invention, the specific parameters for spraying the polymer solid electrolyte onto the current collector using the melt-blowing method in S2 include: the receiving angle of the transmission receiver for the melt-blown filament bundle is 0~90°, the receiving distance is 10~60cm, the spinneret aperture is 0.15~0.4mm, the compressed air temperature is 250~300℃, the melt-blowing temperature is 220℃~300℃, and the time is 2min~6min.

[0038] As a preferred embodiment of the present invention, the method for preparing the positive electrode of a lithium battery comprises: S1: mixing 2-phenylethylene sulfonate, aluminum chloride, LiTFSI and a first organic solvent, and performing a polymerization reaction at 60-80° C. to obtain a mixed solution; S2: The mixed solution is sprayed onto a current collector by a melt-blowing method, and after drying, a current collector having a three-dimensional porous structure is obtained.

[0039] S3: Mix the positive electrode main material, the conductive agent, the binder and the second organic solvent, and apply the obtained mixed slurry on the three-dimensional current collector obtained in S2, and obtain the lithium battery positive electrode after drying; the mass ratio of the polymer solid electrolyte to the positive electrode composite material is (3~4): (6~7).

[0040] In a third aspect, the present invention provides a solid-state battery, comprising the lithium battery positive electrode.

[0041] The lithium battery positive electrode and its preparation method and solid-state battery provided by the present invention, by designing a current collector with a three-dimensional structure, the positive electrode composite material is infiltrated into the three-dimensional skeleton, and can penetrate each other to achieve the effect of conducting both electrons and ions. At the same time, the three-dimensional structure can limit the agglomeration of active substances, so that the active substances can maintain a good dispersion state during the charging and discharging process. This helps to maintain the reactivity of the active substances and improve the performance stability of the battery. DETAILED DESCRIPTION

[0042] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0043] Unless otherwise specified, the various raw materials used in the examples and comparative examples are commercially available conventional raw materials, and the technical means used are conventional means well known to those skilled in the art.

[0044] Example 1 This embodiment provides a lithium battery positive electrode, and the preparation method thereof comprises the following steps: S1: 2 g of 2-phenylethylenesulfonyl fluoride, 0.02 g of aluminum chloride, 1.2 g of LiTFSI and 20 mL of DMF were added to a reaction bottle equipped with a magnetic bar, which was sealed and placed in an oil bath. The mixture was polymerized at 70° C. for 6 h to obtain a mixed solution.

[0045] S2: Use melt-blowing method to spray the mixed liquid onto the current collector aluminum foil, and after drying, obtain a current collector with a three-dimensional porous structure, wherein the acceptance angle of the transmission receiver to the melt-blown filament bundle is 60°, the acceptance distance is 30 cm, the spinneret aperture is 0.2 mm, the compressed air temperature is 260°C, the melt-blowing temperature is 240°C, the time is 4 minutes, and the porosity of the three-dimensional structure is 55%.

[0046] S3: 4g NCM811, 0.5g SP, 0.5g PVDF5130 and 4mL NMP were placed in a homogenizer and mixed evenly, then coated on the three-dimensional current collector obtained in S2, dried for 45 minutes using an infrared drying flat plate coater, and then transferred to a vacuum drying oven to dry overnight. Among them, the mass ratio of the polymer solid electrolyte in S1 to the positive electrode composite material in S3 is 3:7.

[0047] Example 2 This embodiment provides a lithium battery positive electrode, and its preparation method is different from the preparation method of embodiment 1 only in that: the mass ratio of the polymer solid electrolyte in S1 to the positive electrode composite material in S3 is 4:6.

[0048] Example 3 This embodiment provides a lithium battery positive electrode, and its preparation method is different from the preparation method of Example 1 only in that: in S2, the mixed solution is introduced into the current collector aluminum foil by using electrospinning, and after drying, a current collector with a three-dimensional porous structure is obtained, wherein the melt-blowing temperature is 220°C, the time is 5 minutes, and the porosity of the three-dimensional structure is 50%.

[0049] Example 4 This embodiment provides a positive electrode for a lithium battery, and the preparation method thereof is different from the preparation method in Embodiment 1 only in that the mass ratio of the polymer solid electrolyte in S1 to the positive electrode composite material in S3 is 1:1.

[0050] Example 5 This embodiment provides a lithium battery positive electrode, and the preparation method thereof is different from the preparation method of embodiment 1 only in that: in S1, 2-phenylethylenesulfonyl fluoride is replaced by an equal amount of allyl allyl sulfonate.

[0051] Example 6 This embodiment provides a lithium battery positive electrode, and the preparation method thereof is different from the preparation method of embodiment 1 only in that: in S1, 2-phenylethylenesulfonyl fluoride is replaced by an equal amount of vinylbenzenesulfonic acid.

[0052] Example 7 This embodiment provides a lithium battery positive electrode, and the preparation method thereof is different from the preparation method in Embodiment 1 only in that: in S1, 2-phenylethylenesulfonyl fluoride is replaced by an equal amount of allyl p-toluenesulfonate.

[0053] Example 8 This embodiment provides a positive electrode material for a lithium battery, and the preparation method thereof is different from the preparation method in Embodiment 1 only in that in S1, 2-phenylethylenesulfonyl fluoride is replaced by an equal amount of 2-acrylamide-2,2-methylpropanesulfonic acid.

[0054] Example 9 This embodiment provides a lithium battery positive electrode, and the preparation method thereof comprises the following steps: S1: 2 g of 2-phenylethylenesulfonyl fluoride, 0.02 g of boron trifluoride, 1.2 g of LiTFSI and 20 mL of NMP were added to a reaction bottle equipped with a magnetic bar, which was sealed and placed in an oil bath, and polymerized at 70° C. for 6 h to obtain a mixed solution.

[0055] S2: Use melt-blowing method to spray the mixed solution onto the current collector aluminum foil, and after drying, obtain a current collector with a three-dimensional porous structure, wherein the melt-blowing temperature is 240° C., the time is 4 minutes, and the porosity of the three-dimensional structure is 55%.

[0056] S3: 4g NCM811, 0.5g SP, 0.5g PVDF5130 and 4mL NMP were placed in a homogenizer and mixed evenly, then coated on the three-dimensional current collector obtained in S2, dried for 45 minutes using an infrared drying flat plate coater, and then transferred to a vacuum drying oven to dry overnight. Among them, the mass ratio of the polymer solid electrolyte in S1 to the positive electrode composite material in S3 is 3:7.

[0057] Example 10 This embodiment provides a lithium battery positive electrode, and the preparation method thereof is different from the preparation method of embodiment 1 only in that the lithium salt additive is replaced with an equal amount of lithium hexafluorophosphate.

[0058] Test example The lithium battery positive electrode prepared in the embodiment is assembled into a solid-state battery, comprising the following steps: 1. Ionic conductivity: The polymer solid electrolyte membrane (CSEs) prepared above was combined with two stainless steel electrodes (SS) to form a SS / CSEs / SS simulated battery for testing. The battery assembly process was carried out in a glove box where the water and oxygen content was less than 0.1 ppm. The electrochemical impedance spectroscopy (EIS) test used a frequency range of 0.01 Hz to 106 Hz to measure the electrochemical impedance of the polymer solid electrolyte at room temperature. The impedance data obtained from the EIS test was used to calculate the ionic conductivity of the prepared polymer solid electrolyte.

[0059] 2. Cyclic stability: The polymer solid electrolyte sheets (CSEs) prepared above are combined with ternary positive electrodes and lithium metal negative electrodes to form button cells. The preparation of the cells is carried out in a glove box. The cells are tested for charge and discharge cycles at a rate of 0.1C, and the attenuation of their discharge capacity is detected.

[0060] The present invention tests the electrochemical performance of the solid-state battery, and the results are shown in Table 1.

[0061] Table 1

[0062] According to Table 1, when the amount of the polymer solid electrolyte used in Example 2 and Example 4 is less than that of the positive electrode composite material, it is helpful to form a three-dimensional positive electrode layer with uniform performance, and improve the effect of conducting both electrons and ions. Example 3 uses electrospinning to construct a three-dimensional structure, which will affect the battery performance to a certain extent compared with the melt-blowing method used in Example 1; the reason is that the use of the melt-blowing method can construct a three-dimensional skeleton, increase the specific surface area, and has a short process flow. The three-dimensional mesh formed is uniform and more conducive to controlling the above-mentioned porosity. Compared with Example 1, Examples 5 to 9 replaced the sulfonate monomers, solvents, catalysts, etc. in the preparation system. The results show that when the sulfonate monomers, solvents, catalysts, etc. within the scope of the present invention are used, the ionic conductivity of the polymer solid electrolyte and the cycle stability of the final battery are equivalent to those of Example 1, and when the sulfonate monomers outside the scope of the present invention are used, the battery performance will be affected to a certain extent. In Example 10, when the lithium salt additive is replaced with an equal amount of lithium hexafluorophosphate, since lithium hexafluorophosphate is very easy to absorb water and deliquesce, the prepared precursor mixture is in a jelly state, which affects the melt-blowing effect and makes it difficult to construct a good three-dimensional structure, thus significantly affecting the electrochemical performance of the battery.

[0063] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A lithium battery positive electrode, characterized in that: include: A positive electrode composite material and a current collector having a three-dimensional porous structure; wherein the positive electrode composite material is partially filled in the pores of the three-dimensional skeleton of the current collector, and the three-dimensional skeleton includes a polymer solid electrolyte.

2. The lithium battery positive electrode according to claim 1, characterized in that: The amount of the polymer solid electrolyte used is less than the amount of the positive electrode composite material; preferably, the mass ratio of the polymer solid electrolyte to the positive electrode composite material is (3-4): (6-7).

3. The lithium battery positive electrode according to claim 1 or 2, characterized in that: The material containing the polymer solid electrolyte is sprayed onto the current collector by a melt-blowing method to form the current collector having a three-dimensional porous structure.

4. The lithium battery positive electrode according to any one of claims 1 to 3, characterized in that The porosity of the three-dimensional skeleton is 40% to 80%.

5. The lithium battery positive electrode according to any one of claims 1 to 4, characterized in that: The preparation method of the polymer solid electrolyte comprises: mixing an unsaturated sulfonic acid ester monomer, a catalyst, a lithium salt and a first organic solvent, and performing a polymerization reaction at 60-80° C.

6. The lithium battery positive electrode according to claim 5, characterized in that: The unsaturated sulfonic acid ester monomer has a structure shown in general formula (I): (I); wherein R and R' are each independently, the same or different, a fluorine atom, a hydroxyl group, a substituted or unsubstituted C1-C6 alkyl group, a substituted or unsubstituted C1-C6 alkoxy group, a substituted or unsubstituted C2-C6 alkenyl group, a substituted or unsubstituted C 6~ C 30 aryl or a group consisting of any of the above groups; R and R' are bonded to form a ring, fused to form a ring or not formed into a ring; Preferably, the unsaturated sulfonate monomer includes one or more of 2-phenylethylenesulfonyl fluoride, 1,3-propane sultone, vinylbenzenesulfonic acid, allyl allylsulfonate, 2,2-difluorovinyl-4-methylbenzenesulfonate and allyl p-toluenesulfonate.

7. The lithium battery positive electrode according to claim 5 or 6, characterized in that: The lithium salt includes at least one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(trifluoromethylsulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium bis(oxalate)borate, lithium difluorooxalateborate and lithium trifluoromethanesulfonate; and / or, the catalyst comprises one or more of aluminum trichloride, palladium chloride, palladium acetate, nickel dichloride, boron trifluoride, triethylamine, ferric bromide, ferric chloride, titanium tetrachloride and tin tetrachloride; And / or, the first organic solvent includes one or more of diethyl ether, ethanol, acetonitrile, N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, tetrahydrofuran, malononitrile, succinonitrile, glutaronitrile, adiponitrile, pimelonitrile, suberonitrile, azelaic acid dinitrile and sebacononitrile.

8. The method for preparing a positive electrode for a lithium battery according to any one of claims 1 to 7, characterized in that: include: S1: mixing an unsaturated sulfonic acid ester monomer, a catalyst, a lithium salt and a first organic solvent, and performing a polymerization reaction at 60-80° C. to obtain a mixed solution; S2: spraying the mixed solution onto a current collector by a melt-blowing method, and obtaining a current collector having a three-dimensional porous structure after drying; S3: mixing the positive electrode main material, the conductive agent, the binder and the second organic solvent, coating the obtained mixed slurry on the three-dimensional current collector obtained in step S2, and obtaining the positive electrode of the lithium battery after drying; Preferably, the first organic solvent comprises one or more of diethyl ether, ethanol, acetonitrile, N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, tetrahydrofuran, malononitrile, succinonitrile, glutaronitrile, adiponitrile, pimelonitrile, suberonitrile, azelaic acid dinitrile and sebaconitrile; the second organic solvent comprises N-methylpyrrolidone; Preferably, the lithium salt comprises at least one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(trifluoromethylsulfonyl imide), lithium bis(fluorosulfonyl imide), lithium bis(oxalate borate), lithium difluorooxalate borate and lithium trifluoromethanesulfonate; preferably, based on the mass of the unsaturated sulfonate monomer, the amount of the lithium salt is 30wt% to 60wt%; Preferably, the catalyst comprises one or more of aluminum trichloride, palladium chloride, palladium acetate, nickel dichloride, boron trifluoride, triethylamine, ferric bromide, ferric chloride, titanium tetrachloride and tin tetrachloride.

9. The method for preparing a positive electrode of a lithium battery according to claim 8, characterized in that: The melt-blowing temperature is 220° C. to 300° C., and the time is 2 min to 6 min.

10. A solid-state battery, characterized in that: The invention comprises the lithium battery positive electrode according to any one of claims 1 to 7 or the lithium battery positive electrode prepared by the preparation method according to claim 8 or 9.

Citation Information

Patent Citations

  • Electrode plate of gel polymer lithium ion battery and preparation method thereof

    CN101714622A

  • Preparation method of three-dimensional porous-carbon structured lithium-sulfur battery cathode composite material

    CN108695497A

  • Composite positive pole piece, preparation method thereof and all-solid-state lithium ion battery

    CN111900456A

  • Composite electrolyte membrane and preparation method and application thereof

    CN112054245A

  • Oxide solid electrolyte membrane, preparation method thereof and solid-state battery containing oxide solid electrolyte membrane

    CN112436182A